The determinants of liquidity of Indian listed commercial banks: A panel data approach - Eissa A. Al-Homaidi; Mosab I. Tabash; Najib H. Farhan; Faozi A. Almaqtari (Cogent Economics & Finance, 2019)
The objective of this study is to examine the liquidity (LQD) determinants of Indian listed commercial banks. The study has applied both GMM and pooled, fixed and random effect models to a panel of 37 commercial banks listed on the Bombay Stock Exchange (BSE) in India for the period from 2008 to 2017. The banks' LQD was taken as a dependent variable which functioned against both bank-specific and macroeconomic determinants. The results indicated that among the bank-specific factors, bank size, capital adequacy ratio, deposits ratio, operation efficiency ratio, and return on assets ratio are found to have a significant positive impact on LQD, while assets quality ratio, assets management ratio, return on equity ratio, and net interest margin ratio are found to have a significant negative impact on LQD. With respect to macroeconomic factors, the results indicated that interest rate and exchange rate are found to have a significant effect on LQD. The Reserve Bank of India (RBI) should give benchmarks for the above mentioned ratios to achieve smooth LQD of commercial banks in India. The study recommended that bankers should consider assets quality in such a way that improves banks' performance. Finally, the current study provides useful insights for bankers, analysts, regulators, investors, and other interested parties on the LQD of listed commercial banks.
Keywords: 330; bank's liquidity; bank-specific factors; macroeconomic determinants; GMM estimation; India